# What is the equation of a circle with center -1 and 2 and radius 4?

Using (x-h)^2+(y-h)=r^2

sub in -1 and 2 for h and k

get sqrt of 4 for r

anser is therefore

(x+1)^2+(y-2)=2^2

Have and Wonderful Day,

Danny

### How do you get the radius from the area of a circle?

Step 1: Measure the center point of the circle Step 2: Draw a STRAIGHT line from the center point to the edge of circle (this can be anywhere) Step 3: The length between the center point and the circle itself is your radius. An easier way to measure this is measuring the length or width from your circle and divide it by 2.

### What are the tangent equations of the circle x2 plus y2 -6x plus 4x plus 5 equals 0 when it cuts through the x axis?

Equation of circle: x^2 +y^2 -6x+4y+5 = 0 Completing the squares: (x-3)^2 +(y+2)^2 = 8 Radius of circle: square root of 8 Center of circle: (3, 2) The tangent lines touches the circle on the x axis at: (1, 0) and (5, 0) 1st tangent equation: y = x-1 2nd tangent equation: y = -x+5 Note that the tangent line of a circle meets its radius at right angles

### How is the circumference and area of a circle related?

Circumference = 2 x pi x radius area = pi x radius squared If you solve the first equation for "radius" and replace this in the second equation, you get the relation between circumference and area. Specifically, the area is proportional to the square of the radius, but it is also proportional to the square of the diameter, of the circumference, or of any other 1-dimensional measure of the circle.

### What is the equation of a circle whose diameter endpoints are at 10 -4 and 2 2 on the Cartesian plane and what are the perpendicular equations to its endpoints showing work?

Endpoints of diameter: (10, -4) and (2, 2) Midpoint which is the center of the circle: (6, -1) Distance from (10, -4) or (2, 2) to (6, -1) = 5 which is the radius of the circle Equation of the circle: (x-6)^2 +(y+1)^2 = 25 Slope of radius: -3/4 Slope of perpendicular equations which will be parallel: 4/3 1st perpendicular equation: y--4 = 4/3(x-10) => 3y = 4x-52 2nd perpendicular equation: y-2 = 4/3(x-2) =>…

### What is the tangent equation line of the circle x2 plus 10x plus y2 -2y -39 equals 0 at the point of contact 3 2 on the Cartesian plane?

Equation of circle: x^2 +10x +y^2 -2y -39 = 0 Completing the squares: (x+5)^2 +(y-1)^2 = 65 Center of circle: (-5, 1) Slope of radius: 1/8 Slope of tangent line: -8 Point of contact: (3, 2) Equation of tangent line: y-2 = -8(x-3) => y = -8x+26 Note that the tangent line meets the radius of the circle at right angles.

### How do you find the radius of a circle if you know the length of a chord and the shortest distance from the center of the chord to the circle?

Imagine if you will a circle with a chord drawn through it and a line running from the center of that chord to the center of the circle. That line is necessarily perpendicular to the chord. This means you have a right triangle whose hypotenuse is the radius of the circle. The radius is thus given by: r = sqrt{(1/2 chord length)^2 + (length of perpendicular line)^2} The actual formula to find the radius is…

### What is the distance from a point on the x axis to the centre of the circle x2 plus y2 -2x -6y plus 5 equals 0 from the same point where a tangent line meets the circle at 3 4?

Equation of circle: x^2 +y^2 -2x -6y +5 = 0 Completing the squares: (x -1)^2 +(y -3)^2 = 5 which is radius squared Center of circle: (1, 3) Tangent line is at right angles to the radius at (3, 4) and meets the x axis at (5, 0) Distance from point (5, 0) to center of circle (1, 3) = 5 units using distance formula

### What is the perpendicular bisector equation of the of the chord y equals x plus 5 within the circle x2 plus 4x plus y2 -18y plus 59 equals 0?

Equation of circle: x^2 +4x +y^2 -18y +59 = 0 Completing the squares: (x+2)^2 +(y-9)^2 = 26 Equation of chord: y = x+5 Endpoints of chord: (-1, 4) and (3, 8) Midpoint of chord: (1, 6) Center of circle: (-2, 9) Slope of chord: 1 Slope of radius: -1 Perpendicular bisector equation of chord: y-6 = -1(x-1) => y =-x+7

### What are the tangent line equations of the circle x2 plus y2 -6x plus 4y plus 5 equals 0 when the circle passes through the x axis?

Equation of circle: x^2 +y^2 -6x +4y +5 = 0 Completing the squares: (x-3)^2 +(y+2)^2 = 8 Radius of circle: square root of 8 Center of circle: (3, -2) Circle makes contact with the x axis at: (1, 0) and (5, 0) Slope of 1st tangent: 1 Slope of 2nd tangent: -1 1st tangent line equation: y = 1(x-1) => y = x-1 2nd tangent line equation: y = -1(x-5) => y = -x+5

### What is the tangent equation of the circle 2x2 plus 2y2 -8x -5y -1 equals 0 when it touches the point 1 -1 on the Cartesian plane?

There are four steps required in solving this: Find the centre of the circle by rearranging the equation into the form (x - Xo)² + (y - Yo)² = r² where (Xo, Yo) is the centre of the circle and r is the radius of the circle - this is done by completing the square for each of x and y; Find the slope m of the radius between the point of contact (Xc, Yc)…

### What is the tangent equation of the circle 2x2 plus 2y2 -8x -5y -1 equals 0 that touches the circle at the point of 1 and -1?

Point of contact: (1, -1) Equation of circle: 2x^2 +2y^2 -8x -5y -1 = 0 Divide all terms by 2: x^2 +y^2 -4x -2.5y -0.5 = 0 Completing the squares: (x-2)^2 +(y-1.25)^2 = 6.0625 Center of circle: (2, 1.25) Slope of radius: 9/4 Slope of tangent line: -4/9 Equation of tangent: y--1 = -4/9(x-1) => 9y--9 = -4x+4 => 9y = -4x-5 Equation of tangent in its general form: 4x+9y+5 = 0

### What are the equations of the tangents to the circle x2 plus y2 -6x plus 4y plus 5 equals 0 at the points where they meet the x axis on the Cartesian plane?

Circle equation: x^2 +y^2 -6x +4y +5 = 0 Completing the squares: (x-3)^2 +(y+2)^2 = 8 Center of circle: (3, -2) Radius of circle: square root of 8 The radius of the circle will touch the points of (1, 0) and (5, 0) on the x axis The tangent slope at (1, 0) is 1 The tangent slope at (5, 0) is -1 Equations of the tangents are: y = x-1 and y = -x+5